2017
DOI: 10.1111/add.13652
|View full text |Cite
|
Sign up to set email alerts
|

Screening, brief intervention and referral to treatment (SBIRT): implementation barriers, facilitators and model migration

Abstract: Aims To identify barriers and facilitators associated with initial implementation of a US alcohol and other substance use Screening, Brief Intervention, and Referral to Treatment (SBIRT) grant program, and to identify modifications in program design that addressed implementation challenges. Design A mixed-method approach used quantitative and qualitative data, including SBIRT provider ratings of implementation barriers and facilitators, staff interview responses and program documentation. Setting Multiple site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 36 publications
4
101
0
1
Order By: Relevance
“…Qualitative evidence of policy entrepreneurs has been noted elsewhere in studies of successful health-care reforms at the state level [52]. This finding is not measured directly by the model, but findings from a SAMHSA crosssite evaluation have noted the importance of SBIRT 'champions' that are critical to implementation and sustainability [53,54]. An alternative and complementary explanation for slow activation after 2008 is the Great Recession.…”
Section: Discussionmentioning
confidence: 94%
“…Qualitative evidence of policy entrepreneurs has been noted elsewhere in studies of successful health-care reforms at the state level [52]. This finding is not measured directly by the model, but findings from a SAMHSA crosssite evaluation have noted the importance of SBIRT 'champions' that are critical to implementation and sustainability [53,54]. An alternative and complementary explanation for slow activation after 2008 is the Great Recession.…”
Section: Discussionmentioning
confidence: 94%
“…Applying this model, Vendetti et al [22] used a mixedmethod approach to study implementation barriers and facilitators in SAMHSA's cohort 1 programs, as well as changes that occurred over time ('model migration'), partly in response to operational challenges. Whereas, historically, SBI programs tended to recruit on-site medical staff to conduct services [in-house generalist (IHG) model], Vendetti et al [22] found that the programs tended instead to hire specifically trained health educators (in-house specialist, IHS) or to contract services through independent addiction treatment agencies (contracted specialist, CS) to provide the expanded continuum of SBIRT services.…”
Section: Program Implementation: Sbirt By the Numbersmentioning
confidence: 99%
“…Whereas, historically, SBI programs tended to recruit on-site medical staff to conduct services [in-house generalist (IHG) model], Vendetti et al [22] found that the programs tended instead to hire specifically trained health educators (in-house specialist, IHS) or to contract services through independent addiction treatment agencies (contracted specialist, CS) to provide the expanded continuum of SBIRT services. Although four programs used IHG models for some pre-screening and other SBIRT functions, all cohort 1 programs migrated toward CS models to increase screening rates and reduce the burden on medical staff.…”
Section: Program Implementation: Sbirt By the Numbersmentioning
confidence: 99%
“…Differences between cohorts reflect changing SAMHSA mandates, as well as alterations based on the experience of earlier funding recipients (see [21]). Although pre-screening was performed at some cohort 1 sites, this service was conducted universally in cohort 3, and there was a tendency to screen for more risk factors.…”
Section: Samhsa's Sbirt Programmentioning
confidence: 99%
“…The process evaluation collected information about which SBIRT services were performed, where they were provided, who delivered them, how they were organized and managed and to whom they were administered. Further, it investigated barriers to, and facilitators of, program implementation and examined how the grant recipients' initially proposed models were actually implemented in the field and how they changed or evolved over time [21]. Finally, the cross-site evaluators developed, tested and implemented a new methodology for assessing the degree of adherence to the evidenced-based protocols that were adopted by the SAMHSA programs [26], an issue critical to the interpretation of analyses of patient/client outcomes.…”
Section: Sbirt Cross-site Evaluationsmentioning
confidence: 99%